2008
DOI: 10.4158/ep.14.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Bone Loss After Withdrawal of Tamoxifen

Abstract: Objective-To assess whether postmenopausal women with breast cancer have a rapid decline in bone mineral density (BMD) after completion of tamoxifen therapy, similar to that seen after estrogen withdrawal.Methods-We initiated a randomized, double-blind, placebo-controlled trial of alendronate (70 mg weekly) in an effort to prevent bone loss associated with discontinuation of tamoxifen therapy. Postmenopausal women with breast cancer were randomly assigned to receive alendronate or placebo for 1 year within 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…() and Nayak et al . () seem to be contradictory; it is known that tamoxifen behaves as a mixed agonist/antagonist of oestrogen receptors depending on the sensitivity of the tissue to oestrogen (Powles et al ., ; Cohen et al ., ).…”
Section: Pharmacodynamics and Pharmacogenomicsmentioning
confidence: 97%
“…() and Nayak et al . () seem to be contradictory; it is known that tamoxifen behaves as a mixed agonist/antagonist of oestrogen receptors depending on the sensitivity of the tissue to oestrogen (Powles et al ., ; Cohen et al ., ).…”
Section: Pharmacodynamics and Pharmacogenomicsmentioning
confidence: 97%
“…However, a rebound phenomenon is suspected. The interruption of tamoxifen combined with the rapid fall in estrogen levels induced by the AI may promote an accelerated loss of BMD following the switch [7,23,24]. McCaig et al [25] reported that stopping tamoxifen and starting AIs results in a significantly greater increase in bone turnover compared with commencing AIs in tamoxifen-naive patients.…”
Section: Annals Of Oncology Original Articlesmentioning
confidence: 99%
“…Whereas tamoxifen is known to counteract BMD loss and to decrease bone fracture rate in postmenopausal women [13], the sequence of T followed by L had the worse effect on BMD. Likely, the interruption of T combined with the rapid fall in estrogen levels induced by L may promote an accelerated bone turnover and loss of BMD following the TL switch [1416]. Indeed, bone turnover biomarkers changes induced by aromatase inhibitors (AIs) occur rapidly after initiation of treatment [1621].…”
Section: Discussionmentioning
confidence: 99%